Differences in left ventricular myocardial function and infarct size in female patients with ST elevation myocardial infarction and spontaneous coronary artery dissection - Krljanac, Gordana; Apostolović, Svetlana; Polovina, Marija; Maksimović, Ružica; Nedeljković Arsenović, Olga; Đorđevic, Nemanja; Stanković, Stefan; Savić, Lidija; Ušćumlić, Ana; Stanković, Sanja; Ašanin, Milika (Frontiers in Cardiovascular Medicine, 2024)
Introduction Differences in pathophysiology, clinical presentation, and natural course of ST-elevation myocardial infarction in female patients due to either spontaneous dissection (SCAD-STEMI) or atherothrombotic occlusion (type 1 STEMI) have been discussed. Current knowledge on differences in left ventricular myocardial function and infarct size is limited. The aim of this study was to assess baseline clinical characteristics, imaging findings, and therapeutic approach and to compare differences in echocardiographic findings at baseline and 3-month follow-up in patients with SCAD-STEMI and type 1 STEMI. Methods This was a prospective multicenter study of 32 female patients (18–55 years of age) presenting with either SCAD-STEMI due to left anterior descending coronary artery (LAD) dissection or type 1 STEMI due to atherothrombotic LAD occlusion. Results The two groups were similar in age, risk factors, comorbidities, and complications. SCAD-STEMI patients more often had Thrombolysis in Myocardial Infarction 3 flow, while type 1 STEMI patients were more often treated with percutaneous coronary intervention and dual antiplatelet therapy. Baseline mean left ventricular (LV) ejection fraction (LVEF) was similar in the two groups (48.0% vs. 48.6%, p = 0.881), but there was a significant difference at the 3-month follow-up, driven by an improvement in LVEF in SCAD-STEMI compared to type 1 STEMI patients (Δ LVEF 10.1 ± 5.3% vs. 1.8 ± 5.1%, p = 0.002). LV global longitudinal strain was slightly improved in both groups at follow-up; however, the improvement was not significantly different between groups (−4.6 ± 2.9% vs. −2.0 ± 2.8%, p = 0.055). Conclusions The results suggest that female patients with SCAD-STEMI are more likely to experience improvement in LV systolic function than type 1 STEMI patients.